Refining Current Scientific Priorities and Identifying New Scientific Gaps in HIV-Related Heart, Lung, Blood, and Sleep Research - Twigg, Homer L. (AIDS Res Hum Retroviruses, 2017)
The National Heart, Lung, and Blood Institute (NHLBI) AIDS Program's goal is to provide direction and support for research and training programs in areas of HIV-related heart, lung, blood, and sleep (HLBS) diseases. To better define NHLBI current HIV-related scientific priorities and with the goal of identifying new scientific priorities and gaps in HIV-related HLBS research, a wide group of investigators gathered for a scientific NHLBI HIV Working Group on December 14–15, 2015, in Bethesda, MD. The core objectives of the Working Group included discussions on: (1) HIV-related HLBS comorbidities in the antiretroviral era; (2) HIV cure; (3) HIV prevention; and (4) mechanisms to implement new scientific discoveries in an efficient and timely manner so as to have the most impact on people living with HIV. The 2015 Working Group represented an opportunity for the NHLBI to obtain expert advice on HIV/AIDS scientific priorities and approaches over the next decade.